Project N.E.W. - N.O.R.M.A.L. NAVIGATING ELECTRONIC WORLD TO NUMEROUS ONLINE RESOURCES OF MODALITY APPROACHES IN LEARNING - Jimenez, Edward (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The advent of the current COVID-19 pandemic almost halted the education process between teachers and students. Nonetheless, the government strived and overcame all the challenges posited by the pandemic and forged forward to continue the learning experience of students. This paper introduces the proposal entitled Project NEW-NORMAL which will provide substantial support in the learning modalities of students and cater the basic needs of teachers and students for the teaching and learning process. Different learning modalities provided various avenues to the learners to the most convenient and available modes of learning to which they preferred to select and experience. Printed learning modality was one the options where provision of self-learning modules is necessary that could stand without the help of the teachers. Likewise, digitized learning modality offered the utilization of technological platform through social networking sites, media, fora, etc. to download the materials provided by the teachers and the Department. The increased of technological and adversity quotients created a strong hold to face the current situation brought by the pandemic.